Professional fulfillment and parenting work-life balance in female physicians in Basic Sciences and medical research: a nationwide cross-sectional survey of all 80 medical schools in Japan - Yuka Yamazaki; Takanori Uka; Eiji Marui (BMC, 2017)
Abstract Background In Japan, the field of Basic Sciences encompasses clinical, academic, and translational research, as well as the teaching of medical sciences, with both an MD and PhD typically required. In this study, it was hypothesized that the characteristics of a Basic Sciences career path could offer the professional advancement and personal fulfillment that many female medical doctors would find advantageous. Moreover, encouraging interest in Basic Sciences could help stem shortages that Japan is experiencing in medical fields, as noted in the three principal contributing factors: premature resignation of female clinicians, an imbalance of female physicians engaged in research, and a shortage of medical doctors in the Basic Sciences. This study examines the professional and personal fulfillment expressed by Japanese female medical doctors who hold positions in Basic Sciences. Topics include career advancement, interest in medical research, and greater flexibility for parenting. Methods A cross-sectional questionnaire survey was distributed at all 80 medical schools in Japan, directed to 228 female medical doctors whose academic rank was assistant professor or higher in departments of Basic Sciences in 2012. Chi-square tests and the binary logistic regression model were used to investigate the impact of parenthood on career satisfaction, academic rank, salary, etc. Results The survey response rate of female physicians in Basic Sciences was 54.0%. Regardless of parental status, one in three respondents cited research interest as their rationale for entering Basic Sciences, well over twice other motivations. A majority had clinical experience, with clinical duties maintained part-time by about half of respondents and particularly parents. Only one third expressed afterthoughts about relinquishing full-time clinical practice, with physicians who were parents expressing stronger regrets. Parental status had little effect on academic rank and income within the Basic Sciences, Conclusion Scientific curiosity and a desire to improve community health are hallmarks of those choosing a challenging career in medicine. Therefore, it is unsurprising that interest in research is the primary motivation for a female medical doctor to choose a career in Basic Sciences. Additionally, as with many young professionals with families, female doctors seek balance in professional and private lives. Although many expressed afterthoughts relinquishing a full-time clinical practice, mothers generally benefited from greater job flexibility, with little significant effect on career development and income as Basic Scientists.